Neutrophil to Lymphocyte Ratio is a Predictive Factor of Malignant Potential for Intraductal Papillary Mucinous Neoplasms of the pancreas. Issue 14 (May 2019) - Ohno, Riki; Kawamoto, Ryuichi; Kanamoto, Mami; Watanabe, Jota; Fujii, Masahiko; Ohtani, Hiromi; Harada, Masamitsu; Kumagi, Teru; Kawasaki, Hideki
Intraductal papillary mucinous neoplasms (IPMNs) are cystic neoplasms with the potential for progression to pancreatic cancer. Accurate prediction of the malignant potential is challenging and a proper treatment strategy has not been well established. Preoperative neutrophil-to-lymphocyte ratio (NLR) is a biomarker of the malignant potential in patients with several types of malignancy. We explored malignant potential in patients with IPMN. The present study included 56 patients aged of 73 ± 9 years (mean ± standard deviation) who underwent curative resection for IPMN from 1996 to 2017. We analyzed the relationship between the characteristics including NLR and malignant component for predicting pathological results. The nonmalignant IPMN group (N = 21) included patients with low-grade dysplasia (LGD) and intermediate-grade dysplasia (IGD), and the malignant IPMN group (N = 35) included patients with high-grade dysplasia (HGD) and invasive carcinoma. In a univariate analysis, NLR ⩾ 2.2 ( P  = .001), prognostic nutritional index (PNI) < 45 ( P  = .016), CA 19-9 > 37 U/mL ( P  = .039), and cystic diameter ⩾ 30 mm ( P  = .010), and mural nodule ( P  = .010) were significantly different between the malignant IPMN and the nonmalignant IPMN groups. Multivariate analysis showed that high NLR (⩾2.2) (odds ratio 9.79; 95% confidence interval: 2.06-45.6), cystic diameter ⩾ 30 mm (4.65; 1.14-18.9), and mural nodule (4.91; 1.20-20.1) were independently predictive of malignant IPMN. These results suggest that preoperative NLR is a useful predictive biomarker for evaluating malignant potential in patients with IPMN.1